Shape Optimization of the Stacked HTS Double Pancake Coils for Compact NMR Relaxometry Operated in Persistent Current Mode - Kim, S. B.; Saito, R.; Takahashi, M.; Park, Y. J.; Lee, M. H.; Oh, Y. K.; Noguchi, S. (IEEE transactions on applied superconductivity, 2016)
The low temperature superconducting (LTS) coils are used in NMR devices, and liquid helium is used for their cooling. It is possible to reduce the operating costs by manufacturing the superconducting magnet that is consisted of the high temperature superconducting (HTS) coil using liquid nitrogen cooling. We have been developing the NMR relaxometry devices using the HTS double pancake coils and operated in the persistent current mode at liquid nitrogen temperature. The required strength and homogeneity of the magnetic field of proposed NMR relaxometry devices are 1.5 T and 150 ppm/cm 3 , respectively. To achieve the target field strength of 1.5 T, it is necessary to increase the numbers of pancake coils and winding turns of each coil, and the large operating current is required as much as possible. In this paper, I c - B properties of HTS wire and superconducting joint are measured to determine the operating current (load line) for the proposed NMR relaxometry devices. Moreover, 3-D finite-element-model-based analysis was carried out to design the stacked HTS magnets for compact NMR relaxometry with downsizing and low cost.